Use of RFID Technology in the Logistic Process of Distribution with the Support of a Dynamic Simulation Software Tool - Hruška, Roman; Chocholáč, Jan; Kučera, Tomáš (Kaunas University of Technology, 2021)
In recent years, the volume of parcels sold electronically has increased significantly. The current pandemic period has amplified this, as the volume of e-shop transactions has grown even more. Due to the COVID-19 pandemic and related restrictive measures, most stone shops are closed in the Czech Republic. Customers most often use e-shops to buy goods. As a result, the volume of parcel transport, which is provided by parcel carriers, is increasing to finish customers. Improving distribution logistics and the entire logistic system are constantly under pressure in the context of existing competition, maintaining the declared level of customer service and increasing volume of parcels. One way to streamline the logistic distribution process is to use RFID technology as one of the automatic identification technologies. The aim of the article is to create the proposal for the use of RFID technology in the distribution process of parcels in order to make it more effective. Simulation software the Witness Horizon will used to achieve the aim. The software uses the dynamic simulation to evaluate the benefits of using RFID technology before its implementation.
Využití technologie RFID v rámci logistického procesu distribuce za podpory dynamického simulačního softwarového nástroje
Keywords: logistic process; distribution; distribution centre; dynamic simulation; parcel; RFID technology; logistický proces; distribuce; distribuční centrum; dynamická simulace; zásilka; RFID technologie